أثر وحدات تدريبية مقترحة لتنمية صفة المرونة على تحسين التموجات لدى السباحين (فئة الكتاكيت، 11 سنة) - دوسن ، يوسف; Supervisor : والي ، عبد النور (Mohamed Boudiaf University of M'Sila, 2025)
الملخص باللغة العربية: أثر وحدات تدريبية مقترحة لتنمية صفة المرونة على تحسين التموجات لدى السباحين (فئة الكتاكيت، 11 سنة) "دراسة ميدانية على سباحين نادي المرجان للسباحة سيدي عيسى". عنوان الدراسة : أثر وحدات تدريبية مقترحة لتنمية صفة المرونة على تحسين التموجات لدى السباحين (فئة الكتاكيت، 11 سنة)، حيث تهدف الدراسة الى الكشف عن تأثير وحدات تدريبية مقترحة في تحسين المرونة في السباحة الحرة لدى فئة الكتاكيت (11سنة)، والتعرف على الفروق ذات الدلالة الاحصائية بين الاختبارات القبلية و البعدية الخاصة بمهارة المرونة في تحسين التموجات لدى المجموعة التجريبية، حيث استخدمنا المنهج الشبه تجريبي ذو المجموعتين (ضابطة-تجريبية)، و تمثلت عينة البحث في 15 سباح تم اختيارهم بطريقة قصدية، حيث طبقت عليهم الوحدات التدريبية المقترحة لتحسين التموجات، واعتمدنا على اختبار سباحة 10 امتار من الحوض الكبير لقياس تحسن التموجات من ناحية تقليل الزمن المستغرق لدى السباحين، و بالنسبة لعملية تحليل البيانات و التحقق من صحة الفرضيات فقد اعتمدنا على برنامج الحزمة الاحصائية للعلوم الاجتماعية (Spss) نسخة 25 في، و بعد القيام بالمعالجة الإحصائية أظهرت نتائج الدراسة أنه توجد فروق ذات دلالة احصائية بين نتائج الاختبارات القبلية و البعدية الخاصة بمهارة المرونة وتحسين التموجات لدى المجموعة التجريبية، و قد أوصت الدراسة بضرورة زيادة الاهتمام بالفئات الصغرى و توفير الوسائل البيداغوجية و التكنولوجية اللازمة للضمان السير الجيد للعملية التدريبية والتطور المستمر. الملخص باللغة الإنجليزية: Abstract The Impact of Proposed Training Units to Develop Flexibility on Improving Undulation in Swimmers Category: Tadpoles, 11 years old A field study on swimmers from Al-Marjan Swimming Club in Sidi Aissa. Study Title: The Impact of Proposed Training Units to Develop Flexibility on Improving Undulation in Swimmers (Category: Tadpoles, 11 years old). This study aims to investigate the effect of proposed training units on improving flexibility in freestyle swimming for the Tadpoles category (11 years old) and to identify statistically significant differences between pre- and post-tests related to flexibility in enhancing undulation among the experimental group. We adopted a quasi-experimental approach with two groups (control and experimental). The research sample consisted of 15 swimmers selected purposively, who underwent the proposed training units to improve undulation. To measure progress in undulation, we used a 10-meter swimming test in a large pool, focusing on reducing the time taken by the swimmers. For data analysis and hypothesis validation, we relied on the Statistical Package for the Social Sciences (SPSS) version 25. After statistical processing, the results revealed statistically significant differences between the pre- and post-test results related to flexibility and undulation improvement in the experimental group. The study recommends increased attention to younger age categories and the provision of necessary pedagogical and technological tools to ensure effective training processes and continuous development. ملخص الدراسة العنوان: أثر وحدات تدريبية مقترحة لتنمية صفة المرونة على تحسين التموجات لدى السباحين (فئة الكتاكيت، 11 سنة). "دراسة ميدانية على نادي المرجان للسباحة سيدي عيسى". أهداف الدراسة: تصميم وحدات تدريبية موجهة لتحسين مرونة الجسم لدى السباحين في فئة الكتاكيت (11 سنة). تقييم تأثير هذه الوحدات التدريبية على تحسين تقنية التموجات لدى السباحين. تقديم توصيات عملية للمدربين حول كيفية دمج تمارين المرونة في البرامج التدريبية اليومية. تعزيز الأداء الحركي للأطفال في السباحة كجزء من إعدادهم للتنافس في المراحل المتقدمة. تحسين الأداء الفني للسباحين: تُعد المرونة من العوامل الأساسية التي تؤثر على كفاءة الأداء الحركي في السباحة، خاصةً في مرحلة الطفولة (11 سنة)، حيث تساهم في زيادة مدى الحركة وتقليل الإصابات (عبد العزيز نمر، 1997، ص 19). التنمية البدنية المُبكرة: التركيز على تنمية المرونة في سن مبكر (فئة الكتاكيت) يُسهم في بناء قاعدة بدنية متكاملة، مما يُحسن من القدرات الحركية المستقبلية للسباحين (كمال عبد الحميد، 1997، ص 67). تصميم برامج تدريبية مُخصصة: تقدم الدراسة وحدات تدريبية مقترحة قائمة على أسس علمية، مما يُفيد المدربين في تطوير خطط تدريبية فعالة لتحسين التموجات (أميرة حسن محمود، 2008، ص 201). منهج الدراسة: تم الاعتماد على المنهج التجريبي ذو المجموعتين منفصلتين وهذا لملائمته لطبيعة الموضوع. مجتمع وعينة الدراسة: تمثل مجتمع دراستنا في جميع السباحين فئة الكتاكيت 11سنة، أما عينة الدراسة فتمثلت في مجموعة من السباحين عددهم 12 تم اختيارهم بطريقة قصديه. اساليب جمع البيانات: تم الاعتماد على الاختبارات (اختبار سباحة حرة لمسافة عشرة (10) أمتار وحساب الزمن المستغرق) كأداة للدراسة. نتائج الدراسة: هناك فروق ذات دلالة إحصائية قبليا وبعديا لدي المجموعة التجريبية في تحسين التموجات. لا توجد فروق ذات دلالة إحصائية قبليا وبعديا لدي المجموعة الضابطة. هناك فروق ذات دلالة إحصائية بعديا لدي المجموعة الضابطة والمجموعة التجريبية في تحسين التموجات. الاقتراحات والافاق المستقبلية: - الاعتماد على الأسس العلمية الحديثة في التدريب وضمان الاستمرارية من اجل الوصول الى المستويات العليا، حيث ان التأكيد على الاسس العلمية عند وضع البرامج التدريبية من حيث اختيار التمارين (تكون مشابهة لحالات المنافسة) والاسلوب وطريقة التدريب والشدة والتكرارات ووقت الراحة والادوات والوسائل المستخدمة له تأثير مباشر على مستوى أداء السباح. - دراسة خصائص مختلف المرحلة السنية قبل وضع أو تسطير أي برنامج تدريبي حيث يساعد ذلك في التعرف على متطلبات هذه المرحلة تسطير السليم للبرامج التدريبية وفق ما متطلبات كل مرحلة عمرية. Searchlight in English Study Summary Title: The Effect of Proposed Training Units to Develop Flexibility on Improving Undulation Performance Among Swimmers (Category: “Kuttaket” – 11 Years Old). A Field Study Conducted at Al-Marjan Swimming Club – Sidi Aissa Study Objectives: To design targeted training units to improve body flexibility in swimmers aged 11 years. To assess the effect of these training units on improving undulation technique among swimmers. To provide practical recommendations for coaches on how to incorporate flexibility exercises into daily training programs. To enhance motor performance in children as part of their preparation for future competitive stages. Improvement of Technical Performance in Swimming: Flexibility is one of the fundamental components that significantly affects the efficiency of motor performance in swimming, especially during childhood (age 11). It contributes to increased range of motion and reduction in injury risk (Abdel Aziz Nimer, 1997, p. 19). Early Physical Development: Focusing on flexibility development at an early age (Kuttaket category) helps in building a comprehensive physical foundation, which improves the swimmers’ future motor abilities (Kamal Abdel Hamid, 1997, p. 67). Design of Specialized Training Programs: This study presents proposed training units based on scientific principles, which can help coaches design effective training plans to improve undulation performance (Amira Hassan Mahmoud, 2008, p. 201). Research Methodology: The study adopted the experimental method using two separate groups, as it is appropriate for the nature of the topic. Study Population and Sample: The study population consisted of all 11-year-old swimmers in the Kuttaket category. The sample included 12 swimmers selected intentionally (purposive sampling). Data Collection Methods: The study relied on testing as a data collection tool—specifically a 10-meter freestyle swimming test, measuring the time taken. Study Results: There were statistically significant differences (pre- and post-testing) in the experimental group regarding improvement in undulation performance. No statistically significant differences were found in the control group (pre- and post-testing). There were statistically significant differences between the control and experimental groups (post-testing) in favor of the experimental group. Suggestions and Future Prospects: Relying on modern scientific foundations in training and ensuring continuity is essential for achieving high-performance levels. Emphasizing scientific principles when designing training programs—including selecting exercises that simulate competition conditions, choosing appropriate training methods, intensities, repetitions, rest periods, and the tools and equipment used—has a direct impact on swimmer performance. Studying the characteristics of each age group before designing or planning any training program helps to identify the specific developmental needs of that stage, and ensures that training programs are aligned with the requirements of each age group.
Keywords: المرونة; فئة الكتاكيت; السباحين